Educational intervention strategy on nutritional habits in older adults - Milian Roque, Walquiria; Díaz Crespo, Miladys; Ramos Rodríguez, Ana Olivia; Miranda Gómez, María de Jesús; Gort Hernández, Magalys (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: In old age, nutrition plays a fundamental role for health and well-being. Objective: to apply an educational intervention strategy on nutritional habits in older adults of the medical office 12 of the San Cristóbal uno popular council, during the period from June 2019 to June 2021. Methods: An educational intervention study was carried out, the universe was constituted by all the elderly, selecting a probabilistic sample through the application of a questionnaire to determine nutritional habits, psychosocial variables and lifestyle were studied, the quality of food and nutritional habits were evaluated after nutritional counseling. Percentage assessment and Chi-square hypothesis test were used for data analysis. Results: Most of the sample was in the age range of 60 to 69 years, female, pre-university school level. The nutritional assessment of obese was more represented, as well as physical disability and hypertension. Within the mode and lifestyle variables, cigarette smoking predominated, income level was good. A minority participated in support groups and families were mostly small. There was an increase in adequate nutritional habits, as well as in food quality, following the educational program. Conclusions: The physical and mental health status of the elderly depends largely on the way they eat.